Living with digestive stomas: strategies to cope with the new bodily reality - Candela Bonill-; Miriam Celdrán-Mañas; César Hueso-Montoro; José Miguel Morales-Asencio; Concha Rivas-Marín; Magdalena Cuevas Fernández-Gallego (Universidade de São Paulo, 2014)
OBJECTIVE: the objective in this study was to describe the strategies developed by digestive stoma patients to cope with their situation.METHOD: a qualitative and descriptive study was undertaken, involving 21 stoma patients living in the provinces of Málaga and Granada (Spain). The informants were selected in accordance with criteria of appropriateness and diversity, through intentional sampling. The data were collected by means of semistructured interviews.RESULTS: the content analysis revealed three categories around which the distinct strategies were developed: Self-care, Adaptation to the bodily change and Self-help.CONCLUSION: the strategies developed are focusing on achieving the effective management of the stoma and are closely linked with the achievement of autonomy. Discovering the strategies applied is fundamental for the nursing professionals to offer high-quality care, centered on people and their process.